Possible protective role of halo nevus in vitiligo - Bonifazi, E. (European Journal of Pediatric Dermatology, 2017)
This is a retrospective study on 16,575 patients between 0 and 16 years old visited from 2006 to 2016 in a Pediatric Dermatology clinic. In this population 63 patients came to observation for the presence of solitary halo nevi, 208 for the presence of vitiligo, in particular 88 cases of segmental vitiligo, 86 of non-segmental vitiligo and 34 cases we considered as focal vitiligo. In the 208 cases of vitiligo we found 34 halo nevi, in particular 8/88 (9.1%) in segmental, 17/86 in non-segmental (19.8%) and 9/34 (26.5%) in focal. 3 out of 63 cases of solitary halo nevi were followed by vitiligo, segmental in 2 cases, focal in the third. Of the 34 cases of halo nevi associated with vitiligo, 3 cases occurred before vitiligo, while the other 32 occurred simultaneously. The mean age of the 63 solitary halo nevi was 10 years, the mean age of the 34 halo nevi appeared with vitiligo was 9 years; the mean age of onset of the 208 cases of vitiligo was 8.1 years without differences between males and females. In all 271 patients, the presence of other autoimmune diseases in the personal history and in that of the first degree relatives was investigated; the positivity of family history for autoimmunity was not different from controls with no vitiligo or halo nevi. The cutaneous extent of vitiligo in the 174 cases without halo nevi was 3.42%, whereas in the 34 cases of vitiligo associated with halo nevi was 2.35%; in particular, the extension of non-segmental vitiligo was on average 4.98% in the 69 cases without halo nevi and 3.05% of the skin area in the 17 cases associated with halo nevi. When a child has solitary halo nevi rarely he/she undergoes vitiligo later on. This is confirmed by the fact that only 3/34 halo nevi associated with vitiligo had appeared before the latter. The presence of halo nevi in non segmental vitiligo seems associated with a later appearance and smaller extension of vitiligo.